EMOSI TOKOH PADA NOVEL WO AI NI ALLAH KARYA VANNY CHRISMA W - Hudzaifah, Uray Siti; Heryana, Nanang; Priyadi, A Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is to know the emotion of the characters in the novel Wo Ai Ni Allah by Vanny Chrisma W. The theory used in this research is related to novel, behavioristic psychology, and emotions. This research uses descriptive method, qualitative study, and behavioristic psychological approach. Based on the data analysis, this research produces a conclusion as follows. (1) Positive emotion of the novel Wo Ai NI Allah by Vanny Chrisma W., the main and additional characters have the emotions of love and joy, (2) negative emotions of the novel Wo Ai Ni Allah by Vanny Chrisma W., the main and additional characters have emotions fear, anxiety, anger, and sadness. The main and additional figures are more dominant in having negative emotions than positive. However, the negative emotion has a major effect on behavior change and the mindset of the main character will be better.Â Keywords: emotions, characters, novel.Â